Nitensidine B affects proteins of the glycolytic pathway and induces apoptosis in cervical carcinoma cells immortalized by HPV16 - Souza, Felipe de Oliveira [UNESP]; Sorbo, Juliana Maria [UNESP]; Regasini, Luis Octavio [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Rosa, Jose Cesar; Czernys, Erica da Silva; Valente, Valeria [UNESP]; Moreira, Thais Fernanda [UNESP]; Navegante, Geovana [UNESP]; Fernandes, Barbara Colatto [UNESP]; Soares, Christiane Pienna [UNESP] (Elsevier B.V., 2018)
Background: Cervical cancer, the fourth most common type of cancer among women worldwide, accounts for approximately 12% of all types of malignancies that affect women. Natural products have contributed significantly to the development of modern therapies; approximately 70% of the drugs available for chemotherapy are naturally based products. Purpose: The purpose of this study was to examine the biological activities of nitensidine B (NTB), a guanidinic alkaloid isolated from the leaves of Pterogyne nitens Tul. (Fabaceae) in a cervical cancer cell line. Methods: In vitro experiments were performed using cervical carcinoma cells immortalized by human papillomavirus type 16 (HPV16, SiHa cells), since epidemiological and molecular studies have demonstrated robust associations between the etiologies of cervical cancer and HPV infection. Cytotoxicity as well as the effect of NTB treatment on intracellular signals of apoptosis, fragmentation of internucleosomal DNA via terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL), and levels of apoptosis effectors (Caspase 3/7) were evaluated. In addition, differential proteomic analysis (iTRAQ) and protein validation using western blot were performed. Results: The cytotoxicity of NTB treatment in the SiHa cell line was concentration-dependent, with the minimum inhibitory concentration of 50% of the cells of 40.98 mu M. In the TUNEL assay, SiHa cell apoptosis with 3/7 caspase activation was reported at 12 h following treatment. Differential proteomic analysis by iTRAQ demonstrated that proteins of the glycolytic pathway, aldolase A, alpha-enolase, pyruvate kinase, and glyceraldehyde 3-phosphate dehydrogenase were underexpressed. Conclusion: These results indicated that NTB could play a role in decreasing glycolysis. Since tumor cells prefer the glycolytic pathway to generate energy, these findings suggest that NTB may be a reliable model for the study of human cervical cancer cell lines immortalized by HPV16, however more experiments can be performed.
Keywords: Cervical cancer; Nitensidine B; Apoptosis; Proteomic analysis; Glycolytic pathway